2016
DOI: 10.1016/j.ajodo.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of tooth movements after palatal miniscrew-supported molar distalization

Abstract: Through support from the anterior palatal region, the maxillary first molars were distalized without anchorage loss. Furthermore, movement was observed in all 3 planes of space with reduction from the posterior to the anterior in the maxillary arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
0
30
0
4
Order By: Relevance
“…Miniscrew-supported appliances have experienced widespread clinical use and various studies have demonstrated their skeletal and dentoalveolar effects. 6,7,10,[15][16][17][18][19][20][21][22][23][24][25][26][27] The present systematic review was conducted to examine the effectiveness of miniscrewsupported appliances for maxillary molar distalization in Class II malocclusion. 21 Prospective 2 MS/Subject (24) Miniscrews placed in the interradicular space Polat-Ozsoy et al, 2008 20 Retrospective BAPA/HP one or 2 MS/subject (31) BAPA/HP Escobar et al, 2007 19 Prospective BSP, 2 MS/subject (30) BSP Gelgor et al, 2007 25 Prospective MSV/MSP one per subject (40) VFV/PFV Kircelli et al, 2006 17 Prospective BAPA, 1 MS/Subject (10) BAPA Gelgor et al, 2004 24 Prospective /One per subject (25) Intramaxillary fixation screw a MS indicates miniscrew; SD, self drilling; ST, self tapping; SDJ, skeletonized distal jet; MD, molar distalization; PMD, premolar distalization; AL, anchorage loss; MISDS, miniscrew implant-supported distalization system with two miniscrews per subject; BAPA, bone-anchored pendulum appliance; MGBM, MGBM system with interradicular miniscrew; DS, distal screw appliance with palatine miniscrew; DJ, distal jet appliance; HP, Hilgers Pendulum; MSV, miniscrew with vestibular force; MSP, miniscrew with palatal force; VFV, vestibular force vector appliance; PFV, palatinal force vector appliance; BSP, bone-supported pendulum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miniscrew-supported appliances have experienced widespread clinical use and various studies have demonstrated their skeletal and dentoalveolar effects. 6,7,10,[15][16][17][18][19][20][21][22][23][24][25][26][27] The present systematic review was conducted to examine the effectiveness of miniscrewsupported appliances for maxillary molar distalization in Class II malocclusion. 21 Prospective 2 MS/Subject (24) Miniscrews placed in the interradicular space Polat-Ozsoy et al, 2008 20 Retrospective BAPA/HP one or 2 MS/subject (31) BAPA/HP Escobar et al, 2007 19 Prospective BSP, 2 MS/subject (30) BSP Gelgor et al, 2007 25 Prospective MSV/MSP one per subject (40) VFV/PFV Kircelli et al, 2006 17 Prospective BAPA, 1 MS/Subject (10) BAPA Gelgor et al, 2004 24 Prospective /One per subject (25) Intramaxillary fixation screw a MS indicates miniscrew; SD, self drilling; ST, self tapping; SDJ, skeletonized distal jet; MD, molar distalization; PMD, premolar distalization; AL, anchorage loss; MISDS, miniscrew implant-supported distalization system with two miniscrews per subject; BAPA, bone-anchored pendulum appliance; MGBM, MGBM system with interradicular miniscrew; DS, distal screw appliance with palatine miniscrew; DJ, distal jet appliance; HP, Hilgers Pendulum; MSV, miniscrew with vestibular force; MSP, miniscrew with palatal force; VFV, vestibular force vector appliance; PFV, palatinal force vector appliance; BSP, bone-supported pendulum.…”
Section: Discussionmentioning
confidence: 99%
“…The paramedian palate is a favored site for miniscrew placement because it has an adequate bone mass which in-turn reduces the risk of damage to anatomic structures such as dental roots, nerves, and blood vessels. 23 In the present review, 11 studies used the paramedian region of the palate to place miniscrews. Appliances with miniscrews placed in the paramedian palate caused distal movement of the molars by more than 5 mm without undesirable side effects on the premolars and incisors.…”
Section: Miniscrew In Interradicular Area Vs Midpalatinementioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of TADs to distalize the whole dentition has been well characterized in the literature. 8 9 10 11 13 15 16 17 18 19 20 21 22 28 29 Reportedly, the amount of maxillary incisor retraction varied from the stationary position to 3.3 mm, mostly falling in the range near 2 to 3 mm. A few studies have even reported mild labial movement of the maxillary incisors after the use of TADs, such as miniscrew-supported skeletal distal jet.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars from the perspective of reducing micro-implant inflammation around the point of view, that the maxillary posterior region of the microscrew implant should be in mucogingival junction or attached gingival, that is, from the alveolar crestabout 4 mm (Tenenbaum & Tenenbaum, 1986;Melsen et al, 2015;Lee et al, 2017). Some scholars measured the cortical thickness of the maxillary posterior root tip to the alveolar crest at 2 mm, 4 mm, 6 mm, 8 mm level, and suggested that the cortical thicker from the alveolar crest can obtain good initial stability, but there is no combination of angle to measure (Duran et al, 2015). In this study, the thickness of cortical bone and bone was measured at 45°, 60° and 90° from the three sites of the alveolar crest at 4 mm, 6 mm and 8 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%